Cal - O'Connor, Pat 1943-; Mirren, Helen 1945- (Maru Entertainment, 2012)
A love story set within the hatred of strifetorn Northern Ireland.
Sprache: engl. - Untertitel: koran., span.
Keywords: Feature films; Foreign films; Love -- Drama; Motion pictures, Irish; Northern Ireland -- Social conditions -- 1969- -- Drama